General and Industrial ManagementGeneral and Industrial Management by FayolHenri, (StorrsConstance, Trans.). London: Pitman and Sons, Ltd., 1949, 110 pp. - Carter, Nancy M. (Academy of Management Review, 1986)
The article reviews the book ?General and Industrial Management,? by Henri Fayol.